Values and labor force participation in the Nordic countries - Axel Hall; Gylfi Zoega (Economics: The Open-Access, Open-Assessment E-Journal, 2014)
The Nordic countries are known for their success in combining an extensive welfare state with high labor force participation. This is explained by the origins and organization of their welfare states, which can be traced to a set of values and beliefs that emphasize the right of women to participate in the labor market. These values are shared by individuals born in other European countries of Nordic parents and may have origins in the Nordic countries' Lutheran heritage.
Keywords: J21; J22; 330; Values; employment; taxes; beliefs